Temple Tracks Labour, Piety and Railway Construction in Asia - Sinha, Vineeta (Berghahn Books, 2023)
The notions of labour, mobility and piety have a complex and intertwined relationship. Using ethnographic methods and a historical perspective, Temple Tracks critically outlines the interlink of railway construction in colonial and post-colonial Asia, as well as the anthropology of infrastructure and transnational mobilities with religion. In Malaysia and Singapore, evidence of religion-making and railway-building from a colonial past is visible in multiple modes and media as memories, recollections and 'traces'.